Pengaruh Strategi Soft Sellling Dan Emotional branding Dalam Membangun Brand image Pada Toko Perlengkapan Kematian Kafani - Mukhammad Nadhif Fuad; Syarif Hidayatullah; Nu’man Robbani; Muhafidhah Novie (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the role of soft selling and emotional branding strategies in building brand image at Kafani Funeral Supplies. The context of this study is a business with a high level of emotional sensitivity, where consumer decisions are influenced by psychological conditions and emotional experiences. The study uses a qualitative approach with a literature study method and a directed literature review design. Data were obtained from national and international journal articles from 2020 to 2025 relevant to the topics of soft selling, emotional branding, and brand image. The results of the study show that soft selling contributes to creating empathetic, non-aggressive marketing communication and is able to reduce consumer psychological resistance. Emotional branding has been proven to strengthen emotional associations and build lasting emotional bonds between consumers and brands. The combination of these two strategies results in a more positive, meaningful, and trusted brand perception among consumers. This study confirms that the integration of soft selling and emotional branding is an important strategy in building brand image for businesses that deal directly with consumers' emotional conditions.